Draft Annual Development Plan of Madhya Pradesh 1973-74 - Planning Commission (Planning Commission, 1973)
Madhya Pradesh is the largest State in the Union. The State covers an area of 4,43,460 sq.kms. end has a population of 41.65 millions as per 1971 census (provisional results). The density of population is 94 per sq.kilometer which is almost half of the All-India average of 182 and lower than that of any other State except Rajasthan, Himachal Pradesh and Nagaland. The proportion of urban population to total population is 16.31 percent, which means that 83.69 percent of the people live in rural areas.
Government of Madhya Pradesh, Planning, Economics and Statistics Department